Brand as social and socio-psychological phenomenon - Lilia Gomolska, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article considers the brand as a socio-psychological phenomenon. The issue of formation of a brand image as a social object in business, in which communication is a part, is covered. The interaction of the consumer with the brand is the essence of brand communication. It is shown that the perception of the brand is due to a variety of social and psychological factors, and it was disclosed that brand communications may affect a person's behavior, shaping his values and needs.Thus it was clarified that brand communication is an important process that affects the changes in consumption patterns and the formation of motivation of a modern person. It was determined that the brand as a social and cultural phenomenon becomes a mean of identification and affects the value orientations and changes in motivational practices.
Keywords: brand; brand communication; socio-psychological phenomenon; social object; brand image; social and cultural phenomenon